The role of forestry in flood management in a Welsh upland catchment - Graham Hall; Roger Cratchley (European Regional Science Association (ERSA), 2005)
Mechanisms of flooding are being investigated in the mountainous catchment of the Mawddach in the Snowdonia National Park of North Wales, where an estimated 300-year maximal flood event in 2001 caused extensive damage to bridges and roads. Interest has centred on the middle course of the river system, where deeply incised valleys cut through the extensive forest of Coed y Brenin. Investigations are combining field hydrological monitoring with modelling of ground and surface water flows. Forestry plantations, now reaching maturity, are found to have significant moderating effects on flooding downstream: Humid microclimates, resulting from cloud catching on steep Atlantic-facing hillslopes, promote prolific moss growth beneath mature conifers. Deep forest brown earth soils have formed, providing an enhanced water storage and buffering effect during storm events. Clear felling leads to rapid soil erosion, with reversion to thin peaty podsols. Areas of floodplain forestry within the deep valleys impede overbank discharges through generation of lateral turbulence. Models indicate a water depth increase of up to 1m in comparison to grassland floodplain. This represents a significant temporary storage capacity during flood events. Natural broadleaf woodland within the riparian zone stabilises river banks and reduces erosion of periglacial gravel deposits which infill the main valleys. Eroded gravel entering rivers can accumulate downstream, reducing the effectiveness of flood defence embankments.
Keywords: 330